AN INVESTIGATION OF HEAT TRANSFER ENHANCEMENT DUE TO PULSED FLOW IN MINICHANNELS - Kumavat, Parth Sanjay (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2023)
The development of current and next generation high performance electronic devices has led to smaller components in more densely packed spaces. The increasing power levels has resulted in ever-increasing heat flux densities which necessitates the evolution of new liquid-based heat exchange technologies. Pulsating flow in single-phase cooling systems is viewed as a potential solution to the problems involving high heat flux densities. A comprehensive review of literature indicates a lack of time-resolved and space-resolved investigations of unsteady flows on heat transfer resulting from the disruption of hydrodynamic and thermal boundary layers associated with pulsating flows. This study aims to bridge the knowledge gap by using experimental and computational methods to investigate the complex flow characteristics of laminar pulsating flows in a heated rectangular minichannel, and couple that analysis with an investigation of the heat transfer performance. Local time and space dependent distributions and spatial distributions of hydrodynamic and thermal characteristics are discussed by focussing on the hydrodynamically and thermally fully developed region of the minichannel. A wide parameter space is investigated with variations of pulsation waveforms, associated frequency and flow rate amplitudes. Experimental analysis involves a uniformly heated thin foil approximating a constant heat flux bottom wall. Local, non-intrusive and high spatial resolution spatial measurements of the heated surface are recorded using an infrared thermography system. Analogous to the experimental conditions, a three-dimensional conjugate heat transfer computational model is developed. A volumetric heat generation source is imposed on the solid domain. Results for the axial velocity profile in response to a symmetric sinusoidal flowrate waveform showed that a parabolic shape was attained, typical of laminar flow. At low, frequency the oscillating velocity profiles was in phase with the axial pressure gradient and bottom wall shear stress. However, as frequency increases, the peaks in the velocity profiles are shifted to the near wall vicinity and there is clear evidence of phase lag between the flowrate and axial pressure gradients as the bulk inertial forces are strengthened. Certain cases of asymmetric sinusoidal and half rectified flowrate waveforms presents evidence of the flow reversal phenomenon in the near wall regions. Consequently, the flow reversal effect promotes the heat transfer as stronger diffusion of heat from wall to bulk region takes place. A greater rise in the friction factor is determined for the non-conventional waveforms Oscillating wall temperature profiles present peak magnitudes in the near wall vicinity for moderate to high frequency range and similar behaviour exists for the oscillating velocities. The space averaged Nusselt number increased with the corresponding rise in the flowrate amplitudes which correlates to stronger, enhanced convection effects. There exists an optimum band of frequencies which reflect enhancements in the time-space averaged heat transfer, whereas the other frequencies show a deterioration. Thus, the moderate-high frequency pulsating flows of all waveforms studied, present an appreciable heat transfer enhancement over the steady flows with a satisfactory thermal performance factor.
APPROVED
Keywords: Heat transfer enhancement; Minichannel; CFD; Infrared thermography; Pulsating flow